Systemic Risk Monitoring ("SysMo") Toolkit-A User Guide - Blancher, Nicolas (IMF Working Papers; Working Paper ;, 2013)
There has recently been a proliferation of new quantitative tools as part of various initiatives to improve the monitoring of systemic risk. The "SysMo" project takes stock of the current toolkit used at the IMF for this purpose. It offers detailed and practical guidance on the use of current systemic risk monitoring tools on the basis of six key questions policymakers are likely to ask. It provides "how-to" guidance to select and interpret monitoring tools; a continuously updated inventory of key categories of tools ("Tools Binder"); and suggestions on how to operationalize systemic risk monitoring, including through a systemic risk "Dashboard." In doing so, the project cuts across various country-specific circumstances and makes a preliminary assessment of the adequacy and limitations of the current toolkit.